2022
DOI: 10.1007/s00382-022-06353-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a long-lasting extreme cold event in Siberia by a minor sudden stratospheric warming and the dynamical mechanism involved

Abstract: Previous studies have paid much attention to the impact of major sudden stratospheric warming (SSW) events on the tropospheric circulation. However, the attention to the modulation of minor SSW events on the extreme cold events is limited. In this study, the extreme cold event in Siberia in the winter of 2000/2001, the longest-lasting one from 1980/1981 to 2019/2020, and its linkages to the minor SSW event have been examined. Our results show that the largest cooling occurred in Siberia during 30 December 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The extension of stratospheric polar vortex to East Asia played an important role in reflecting the planetary wave during SSW event. Liu et al (2022) found that the reflection of planetary wave led the deepening of trough in the Atlantic-Euro region by about 2 days during the ECE in the winter of 2000/2001. Nath et al (2016) showed that the strengthening of trough in central Eurasia and the reflection of planetary wave occurred nearly synchronously during the 2013 SSW event.…”
Section: Possible Dynamic Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…The extension of stratospheric polar vortex to East Asia played an important role in reflecting the planetary wave during SSW event. Liu et al (2022) found that the reflection of planetary wave led the deepening of trough in the Atlantic-Euro region by about 2 days during the ECE in the winter of 2000/2001. Nath et al (2016) showed that the strengthening of trough in central Eurasia and the reflection of planetary wave occurred nearly synchronously during the 2013 SSW event.…”
Section: Possible Dynamic Mechanismsmentioning
confidence: 98%
“…Liu et al . (2022) found that the reflection of planetary wave led the deepening of trough in the Atlantic‐Euro region by about 2 days during the ECE in the winter of 2000/2001. Nath et al .…”
Section: The Role Of Sswmentioning
confidence: 99%
“…The zonal‐mean zonal wind and temperature obtained from ERA5 reanalysis were used to classify SSW events (Liu et al., 2022). Figure 1 shows the zonal‐mean temperature at 60°N and 90°N at 10 hPa during quiet, minor warming and major warming periods.…”
Section: Classification Of Sswmentioning
confidence: 99%
“…Additionally, stratospheric sudden warming events also induce blocking anomalies via stratospheric signal downwelling (Lu & Ding, 2013). Specifically, during sudden stratospheric warming events, the downwelling of stratospheric westerly anomaly signals and the northward shift of westerly winds contribute to an increased frequency of blocking in the Pacific Northwest (Liu et al, 2022). A recent study reported an increasing trend in concurrent blocking, which plays an important role in strong ECEs (Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%